(untitled) (Research, Society and Development, 2021)
The present study has the theme “Pedagogical Practices: Contributing to the education of students with Autism Spectrum Disorder (ASD). And as the main Objective to describe a literature review on the importance of pedagogical practices for the evolution of the student with Autism Spectrum Disorder (ASD), in relation to access and materials adapted to the child with autism in regular school. It is a bibliographic article that will initially address a brief history and description of the stages of the ASD, then reports on the Pedagogical Practices for a meaningful inclusion of the child with ASD, after addressing the importance of the Materials adapted to evolve the student with TEA. Material and Methods: were selected through electronic searches and searches, articles, magazines and books. In this context, it can be said that for school inclusion it is necessary for the school to fully meet the specificity of this child, so that it can guarantee the access / permanence of the child with autism in the school environment, as well as develop their autonomy, interactions, and their potential. Researching TEA and inclusion contributes to expanding knowledge in the area, however it is necessary to comply with and comply with the Legislation and Public Policies aimed at this student. In this perspective, the theme reaffirms the relevance, that everyone understands and accepts human diversity, and can contribute to the construction of a fair and egalitarian society. Because giving children with autism the opportunity to live with others of the same age group contributes to stimulating their interactive abilities. No less relevant, the pedagogical practices offered to this student are decisive for their cognitive and social evolution, that is, all strategies and resources are fundamental in the construction of a better quality of life in all its aspects. Final Considerations: The present study sought to describe the importance of Pedagogical Practices for the evolution of students with ASD, seeking to expand new knowledge on the subject and the benefits of including this student in regular education.